Recall Compliance in the Clinical Periodontics Section of the University of the Philippines College of Dentistry Academic Year 2018-2019/Franchette Mae T. Ladera and Seleena V. Lim. - Lim, Seleena V.; Buenaventura, Criszel F.
Introduction. Compliance with appointments is necessary for maintenance of oral health. In Clinical Periodontics, recall appointments are a crucial part of the treatment plan. Hence, the aim of this study is to determine the recall compliance in the Clinical Periodontics Section of the University of the Philippines College of Dentistry within the A.Y. 2018-2019.